Era Revolusi Indsutri 4.0 dan Eksistensi Pendidikan Islam - Imamuddin M.; Zaharuddin M.; Andryadi Andryadi; Isnaniah Isnaniah; Febria Sri Artika (State Islamic Institute of Madura, 2022)
This paper is intended to analyze the presence of Islamic education in the era of Industrial Revolution 4.0. The researchers used the Library Research in this paper. Data collection was carried out by reviewing and examining printed and electronic books, journals, and documents as data sources and other relevant information. Islamic education as an Islamic-based educational institution needs to take a range of steps and approaches to preserve its presence in the 4.0 period of the Industrial Revolution, so as not to fall into various competitions. Based on the analysis, there are several strategies that must be followed by Islamic education to sustain its existence, namely: designing innovative Islamic education, reforming and renewal Islamic education, enhancing capabilities in technology and literacy, and the concept of integration and interconnection of Islamic education